Masterplan for Developing Human Capital of Tahfizh Teachers at Daarul Qur'an: Rencana Pengembangan Sumber Daya Manusia Guru Tahfizh di Daarul Qur'an - Cahyono, Teguh Catur; Rahmawati , Imelda Dian (Indonesian Journal of Education Methods Development, 2024)
This research explores the development of human capital for Tahfizh teachers at Pesantren Tahfizh Daarul Qur’an in Malang, East Java, addressing the unique qualifications required for these educators. While general teachers must possess pedagogical competence as mandated by law, Tahfizh teachers must also attain core competencies related to the memorization of the Quran, underpinned by traditional knowledge and lineage known as Sanad Al-Qur'an. The study employs a qualitative, descriptive-explorative design to analyze the master plan for human capital development. The findings reveal a structured approach to enhancing Tahfizh teachers' competencies, encompassing pedagogical, social, personal, and professional aspects. The development process is organized into three stages: improving reading (tahsinul qiro'ah), strengthening memorization (itqonul hifzh), and acquiring the Quranic sanad from historical figures. By establishing quality standards for Tahfizh teachers' human capital, this research aims to elevate the quality of Tahfizh education, thereby positively influencing the overall performance of the institution. The study underscores the importance of specialized training for Tahfizh teachers in contributing to effective Quranic learning environments. Highlights: Unique Competencies: Tahfizh teachers require both pedagogical skills and Quranic memorization expertise, emphasizing the need for specialized training. Structured Development: The human capital development plan includes three stages: improving reading, strengthening memorization, and acquiring the Quranic sanad. Performance Enhancement: A focus on quality standards for teachers aims to improve Tahfizh education and overall institutional performance. Keywords: Tahfizh, Sanad, Human Capital, Education, Competencies